Determination of the efficiency and the total loss coefficient of the 2m2 flat plate collector, using a test bench according to NTP 399.400 in Arequipa - Flores Larico, Pedro Bertín (2020)
Arequipa is a peruvian south city with more than 70000 Solar Energy Water Heating Systems (know in spanish as SCAES). In this area there are more than 30 solar thermal manufacturers. They do not have laboratories to collet  standarized data about  characteristics and efficiency of their SCAES. In this research, a group of test was installed to evaluate the efficiency of three flat plat solar collectors (2m2). This study was made under the Peruvian technical standard NTP 399.400 2001. As result, the range of maximum efficiency values and the global coefficient of losses of the SCAES was found.